Pelatihan Pentingnya Pemahaman Informasi Penggalian Data (Data Mining) Di Era Digitalisasi Saat Ini - Sovina, Mutiara; Harahap, Faisal Amir; Lazuly, Ivi; Akbar, Muhammad (LPPM Universitas Potensi Utama, 2025)
The digitalization era has brought significant changes in how information is collected, processed, and utilized. One of the key fields in managing this information is data mining. However, many individuals, particularly in educational environments and the general public, still lack a proper understanding of the concepts and practical applications of data mining. This community service activity aims to provide training and basic knowledge about data mining and its benefits in data-driven decision-making. The training targeted teachers and high school students, using a combination of lectures, interactive discussions, and hands-on practice with simple data mining tools. The results showed an increased understanding among participants regarding data mining concepts, workflows, and real-world applications, particularly in education and social contexts. This training is expected to serve as an initial step in building strong data literacy within the community to face the challenges of the digital era intelligently and productively.